4 - Les Limites sectorielles de l’Expérience togolaise de vingt ans de "Planification" : l’Agriculture (1966-1985): by Ewihn-Liba Pana - Ewihn-Liba Pana (Africa Development, 1989)
In Togo, planning of national development on a long teim basis spans over a period of 20 years ending in 1985 when faced with economic crisis, the country adopted a structural adjustment programme. A retrospective assessment of planification of the agriculture sector, the sector which was considered "the priority of priorities" by successive plans since independence tends to indicate a big gap between policy proclamations, investments and the outcome. The slow progress of agriculture and even the drastic regression can be explained by the marginalisation of the peasantry. In the 1970' s the Agricultural sector witnessed profound changes such as limits in access to land by the peasantry following rapid population growth and those that resulted from types of development strategies adopted which conceived agriculture as a source of foreign exchange and not a sector meant to feed the nation. With the exception of the consumption by industrial enclaves and urban centers, all production destined to the local market and to meet the local needs was considered a waste. Commercial crops were privileged and benefitted from most of the foreign investment in the sector. Contrary to proclamations of achieving food self-sufficiency by 1980, the food sub-sector has undergone a decline. A tho- rough assessment of these trends is rendered difficult by the lack of reliable quantitative data on Togolese agriculture. Besides production of provisional statistics in the cosy atmosphere of ministerial offices neglects the human factor in rural development. Without the know-how and the consent of the peasantry, nothing can be achieved in the rural areas.